Efficacy Of Eel Cookies On Improving Nutritional Status Of Pregnant Women With Chronic Energy Defifiency - Devi Pratiktowati; Dewi Marhaeni Diah Herawati; Ginna Megawati; Deni Kurniadi Sunjaya (Jurnal Kesehatan Prima, 2020)
A high prevalence chronic energy deficiency (CED) in pregnant women exist in Indonesia, which approximately 16.2%. The government had made various efforts to eliminate CED in pregnant women. Therefore, our study aimed to analyze the efficacy of eel cookies on improving nutritional status of pregnant women with CED risk. An experiment with a pre-post design of 36 pregnant women with risk of CED in Ciletuh, Sukabumi was carried out for 30 days. Pregnant women in intervention group were given eel cookies, while control group were given cookies without eel. At the beginning and end of the study, MUAC were measured and food intake was assessed through a 24 hour recall. The research data was analysed using t-test, Mann-Whitney test and chi square. Significant difference in body weight between intervention and control groups was not found (p > 0.05). The mean bodyweight in intervention group after intervention (48.5) was higher than in control group (48.3). The Mean bodyweight and MUAC in the two groups before and after intervention also did not show a significant difference  (p> 0.05). The risk of CED in pregnant women who received eel cookies were lower compared to the control group. Consumption of eel cookies can reduce CED risk in pregnant women by 35%, while cookies without eel only reduce the risk by 29.4%. Eel cookies had higher efficacy compared to cookies without eel on reducing CED risk in pregnant women.